Bone mineral density is related to lung function outcomes in young people with cystic fibrosis—A retrospective study. Issue 12 (30th October 2017) - Smith, Nathan; Lim, Angelina; Yap, Matthew; King, Louise; James, Simon; Jones, Alicia; Ranganathan, Sarath; Simm, Peter
Abstract: Introduction: Improvements in the medical management of cystic fibrosis (CF) in recent years have resulted in increased prevalence of long‐term sequelae of the condition, such as low bone mineral density (BMD) and hence an increased risk of fractures in later life. Aim To explore the interaction between BMD and lung function, nutrition, and genotype. Methods: This study was a retrospective audit of 202 children with CF from August 2000 to January 2016 to investigate associations between BMD Z‐scores with clinical status, nutrition, and genetics using dual‐energy absorptiometry X‐ray data from the Royal Children's Hospital Melbourne, Australia. Results: Severity of both lung disease ( P < 0.0001) and nutritional status ( P < 0.05) was found to be strongly associated with BMD Z‐scores. Conclusions: This is the biggest study to date to provide further evidence that the severity of pulmonary disease is related to BMD in CF patients and therefore screening guidelines for bone health in children with CF should target individuals with the poorest clinical status.